Letter (copy) : Ray Cox Memorial - Citrine, Walter, 1887-1983
042-0082-001 WMC/WJB/AC/286 International 21st December, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, RAY COX MEMORIAL. I am in receipt of your letter of 20th instant, explaining what has happened in regard to the photograph of the Ray Cox Memorial. I am sending a copy of your letter to the Joint Council of the Southampton Trades Council, Labour Party and Co-operative Party, so that they may understand that the fault lies neither with yourself nor with us. Probably as the result of your letter, it will be possible, after all, to send them the promised photograph. Yours faithfully, General Secretary. 292/946/42/82